BUDAYA KERJA, DISIPLIN KERJA DAN KOMITMEN KERJA TERHADAP KINERJA GURU ASN DI SMPN 3 SITUBONDO DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Khoriratul Atiyah; Ika Wahyuni; Ediyanto Ediyanto (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
This research uses a quantitative approach with an explanatory method. The population in this study was all thirty twu ASN teachers at SMPN 3 Situbondo. The sampling technique used saturated sampling, where all members of the population were used as samples. Data analysis and hypothesis testing used Partial Least Square Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0 application. The research results show that Work Commitment has a positive and significant effect on Job Satisfaction, while Work Culture and Work Discipline do not significantly affect job satisfaction. Furthermore, Work Discipline has a positive and significant effect on Teacher Performance, but Work Culture and Work Commitment do not significantly affect teacher performance. Job Satisfaction also does not significantly affect teacher performance. Subsequently, Work Culture, Work Discipline, and Work Commitment do not significantly affect teacher performance through job satisfaction. This research concludes that Teacher Work Commitment is very important in increasing job satisfaction, but Work Culture and Work Discipline factors require further attention for a more significant impact on job satisfaction. An increase in Work Discipline directly correlates with an increase in teacher performance. However, job satisfaction has not been able to become a significant mediator in improving teacher performance.